Question #fca5a

1 Answer
Jul 23, 2017

(3)
vec a xx vec b + vec b xx vec c + vec c xx vec a = 3(vec c xx vec a)a×b+b×c+c×a=3(c×a)

Explanation:

Given that vec a + 2vec b + 3vec c = vec Oa+2b+3c=O

Now, Taking cross product or **vector product ** with vec a a on both sides:-

(vec a + 2vec b + 3vec c ) xx vec a = vec O xx vec a(a+2b+3c)×a=O×a

Since cross product is distributive and cross product with vec OO OR null vector is vec OO itself,

=> vec a xx vec a + 2(vec b xx vec a) + 3(vec c xx vec a) = vec Oa×a+2(b×a)+3(c×a)=O

because the cross product of a vector with itself is null vector or vec O therefore vec a xx vec a = vec O

=> 2(vec b xx vec a) + 3(vec c xx vec a) = vec O ------------------- 1.

Similarly, taking cross product with vec b and vecc on both sides:-

(vec a xx vec b) + 3(vec c xx vec b) = vec O ------------ 2.

(vec a xx vec c) + 2(vec b xx vec c) = vec O ------------ 3.

Adding 1., 2. and 3.

2(vec b xx vec a) + 3(vec c xx vec a) + (vec a xx vec b) + 3(vec c xx vec b) + (vec a xx vec c) + 2(vec b xx vec c) = vec O

Now for any two vectors vec x and vec y, color(red)(vec x xx vec y = - vec y xx vec x).

Also, sum of any vector with null vector is the vector itself.

=> (vec a xx vec b) - 2(vec a xx vec b) + 2(vec b xx vec c) - 3(vec b xx vec c) + 3(vec c xx vec a) - (vec c xx vec a) = vec O

=> -(vec a xx vec b) - (vec b xx vec c) - (vec c xx vec a) + 3(vec c xx vec a) = vec O

=> -(vec a xx vec b) - (vec b xx vec c) - (vec c xx vec a) = - 3(vec c xx vec a)

Taking product on both sides with -1,

=> vec a xx vec b + vec b xx vec c + vec c xx vec a = 3(vec c xx vec a)